Values Education in J. Drost's Perspective - Pujianto, Rizky; Hidayat, Rakhmat (Baileo: Jurnal Sosial Humaniora, 2024)
This study explores J. Drost’s perspective on values-based education, emphasizing values as the core foundation of the school system. Through a structured literature review, this research analyzes Drost’s writings by identifying primary texts, conducting critical comparisons, and synthesizing the strengths and weaknesses of his educational thought. Colossus Gonzaga School is presented as a concrete manifestation of Drost’s philosophy, offering an alternative educational model that places human dignity and moral values at the center of the learning process. Drost’s ideas emerged in contrast to the authoritarian and instrumental nature of education during Indonesia’s New Order regime, proposing instead a liberating, humanistic framework. The study finds that Drost’s vision aligns with broader efforts in Indonesia to reorient education as a tool for personal and social emancipation, as seen in the works of Ki Hadjar Dewantara, Moh. Syafei, and Father Mangun. The novelty of this study lies in its comprehensive reconstruction of Drost’s contributions within both historical and pedagogical contexts, highlighting how his values-based approach continues to resonate in contemporary educational discourse. This research offers relevant insights for developing social and humanities scholarship by reaffirming the importance of value-driven education as a response to technocratic and depersonalised schooling models.